(untitled) (Praxis Educativa, 2019)
In this article we advocate for the pedagogic potential of educational research, as it educates in a particular manner on the meaning of investigation and the set of consents and permits—as well as exclusions—which are expected in its manifestations. From such grounds we will try to discern between those practices that reinforce coloniality in the academy and the gestures which involve opportunities for disruption and escape from traditional category oppressions. We hope an inventory of decolonial practices (even those which are tacitly included as such) will contribute with the (re) institution of narratives along the lines of Catherine Walsh’s politics of naming (Walsh, 2014) and what the most radical research paradigms discuss as (contested) interventions in the representations of reality (Denzin & Lincoln, 2011, 2012; Kincheloe & McLaren, 2012). In this sense, the article itself represents a decolonizing text, imbued with pedagogic force.